Viviana Martinez-Bianchi Oral History Interview, 2024 - Martinez-Bianchi, Viviana (2024)
This oral history interview with Dr. Viviana Martinez-Bianchi was conducted on January 26, 2024 by Fiorella Orozco as part of the Bass Connections Agents of Change Oral History Project.